Sphenempis, a new Empis subgenus (Diptera, Empididae) from the Eastern Palaearctic Region - Saigusa, Toyohei (Zootaxa, 2022)
Empis (Sphenempis Saigusa) subgen. nov. (Diptera, Empididae) and its included species, Empis (Sphenempis) bicoloriventris Saigusa sp. nov. from the Ryukyus, Japan and Empis (Sphenempis) oshimai Saigusa sp. nov. from Kyushu, Japan are described. Empis (Lissempis) amurensis Shamshev, 1998 from Amur, Russia is newly included in the subgenus Sphenempis.